2016
DOI: 10.1186/s13639-016-0041-y
|View full text |Cite
|
Sign up to set email alerts
|

A low-power wireless system for energy consumption analysis at mains sockets

Abstract: Introduction: Improving energy efficiency and reducing energy wastage is an important topic of our time. But it is quite difficult to figure out how much of our total electricity bill can be mapped to which device or at what time the device used it. We believe energy efficiency of normal households can be improved, if this kind of transparency would be available. In this article, we present a system for energy measurement at mains sockets to gain a transparent view of energy consumption for each device in a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…15.4 in the 868 MHz band, but only mentions that latency bounded operations are limited due to duty cycle operations. Another example, [12], describes a protocol to analyze power consumption at mains sockets. There, it is shown that radio duty cycle regulations are responsible for the limitation of the amount of clients connected to a master device, but the extend of this limitation is not verified with experimental data.…”
Section: Related Workmentioning
confidence: 99%
“…15.4 in the 868 MHz band, but only mentions that latency bounded operations are limited due to duty cycle operations. Another example, [12], describes a protocol to analyze power consumption at mains sockets. There, it is shown that radio duty cycle regulations are responsible for the limitation of the amount of clients connected to a master device, but the extend of this limitation is not verified with experimental data.…”
Section: Related Workmentioning
confidence: 99%